Nutrient Enrichment Impact of Wastewater Shrimp Ponds on Coral Reefs of Nyamplungan Village, Karimunjawa - Raja Aditya Sahala Siagian; Agus Sabdono; Sunaryo Sunaryo; Agus Trianto; Dio Dirgantara (Marine Science Department Diponegoro University, 2022)
Increased nutrients can cause a rise prevalence in coral disease. Shrimp pond wastewater can produce nitrate, phosphate, and ammonia from the residual of the feeding and shrimp feces. Nyamplungan village, Karimunjawa was selected as the study site as it represents a location with shrimp pond activity that close to coral reef ecosystem. This study aims to examine the difference of disease prevalence, coral cover, and coral genus diversity at ±300 m and ±1000 m from the shrimp pond and to examine the relationships between disease prevalence and nutrients (nitrate, phosphate, ammonia). Coral disease prevalence was measured within a modified 30 x 2 m belt transect at six sampling stations. Station 1, 2, and 3 were 6-8 m in depth (±1000 m from the shrimp pond), then station 4, 5, and 6 were depth 1-3 m (±300 m from the shrimp pond). Coral genus diversity was conducted by using the Roving Diver Visual Method. Coral cover was measured within Line Intercept Transect (LIT) 30 m. The results show that station 5 had the highest disease prevalence (30.80%±2.78%). Station 1 had highest coral cover (90.87%±7.16%). Coral genus diversity had a medium category for each station. Disease prevalence was significantly different between station depths of 1-3 m (±300 m to the shrimp pond) and depths 6-8 m (±1000 m from the shrimp ponds) (P<0.05). Disease prevalence had strong relationship with nitrate (r= 0.975), phosphate (r= 0.972) and ammonia (r= 0.958). These results suggest that the continuation of coral monitoring with additional disease incidence and disease progression, temporally.